Laboratory tests of muristerone A on various insects (Bollettino di zoologia agraria e bachicoltura, 2024)
This study reports the assays on the ecdysonic and toxic activity of a phytoecdysone heptahydroxy (2β, 3 β, 5β, 11α, 14 α, 20 R, 22 R)-colest-7-en-6-one or muristerone A, extracted from the seeds of a plant of the genus Ipomoea.The assays demonstrated that the product is effective on all the species treated (Quadraspidiotus perniciosus Comst., Ostrinia nubilalis Hb., Plodia interpunctella L., Galleria mellonella L., Spodoptera littoralis (Boisd.), Bombyx mori L., Tenebria molitor L., Tribolium confusum Duv., Apis mellifera ligustica Spin.), but that the effect varies with the instar and species. This effectiveness is mainly ascribed to an action of the ecdysonic type, and is stronger in larval forms.The achievement of homogeneous results reproducible on a larger scale depends not only on the factors described above, but also on the choice of the time and mode of administration.